The Influence of Service Quality, Promotion, and Trust on Shopee Food Consumer Satisfaction - Septi Herawati; Evan Saktiendi; Cut Nisa Azzahra (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this research is to determine the partial and simultaneous influence of Service Quality, Promotion and Trust on Shopee Food Consumer Satisfaction. The sampling method in this research is non-probability sampling with a purposive sampling technique. The analytical tools used are validity test, reliability test, classical assumption test, multiple linear regression (R2), t test, f test, and coefficient of determination. The testing tool used is SPPSS 26. The results of this research show that the t test results for Service Quality, Promotion and Trust partially influence Consumer Satisfaction, while the f test results for Service Quality, Promotion and Trust simultaneously influence Consumer Satisfaction.